Auction Practices Viewed from Islamic Business Law - Jamaludin Jambunanda, Ahmad; Wiratama, Reva; Sunardi, Dedi (MUAMALATUNA, 2023)
Auction is a system of buying and selling transactions with certain terms and conditions that are adjusted to the agreed contract between the seller and the buyer. The auction system is also explained in Islamic law. So this study aims to determine the auction technique with Islamic business law. Islamic business law is a provision that explains the rules of trading with Islamic advice according to the guidelines of the Al-Qur'an and As-Sunnah. One of them is the discussion of auction practices in Islamic business law which is often carried out by today's society. Auction practice is part of the process of buying and selling goods using different techniques, but having certain terms and conditions in common. In fact, the practice of auctions is approved and permissible with clear Islamic business law recommendations and does not have a negative impact in the future. The community needs to understand and carry out auction practices in accordance with the requirements and provisions that apply to Islamic business law.